Workload Analysis and Green Human Resource Management on Employee Performance - Anugrah, Rafa; Kokom Komariah; Faizal Mulia Z (Universitas Pamulang, 2024)
The manufacturing industry sector is an industrial sector in Indonesia that is developing and contributes to the industry nationally, therefore companies engaged in this field must be able to face competition which is the impact of the growing industry. So that human resources are an important part of the company, if the human resources are lacking, the company's target in achieving its goals will not be carried out PT. ASTRA INTERNATIONAL Tbk Isuzu Sukabumi - Bogor. Tbk Sukbumi -Bogor is a company engaged in the automotive manufacturing industry that has problems with employee performance. This study aims to find out whether workload and green human resource management have an influence and impact on employee performance at PT. ASTRA INTERNATIONAL Tbk Isuzu Sukabumi - Bogor. The research method used is a quantitative method using descriptive and associative methods. The data source used by conducting interviews and distributing questionnaires as a tool in obtaining data and samples was used namely saturated sampling to 31 respondents of PT. ASTRA INTERNATIONAL Tbk Isuzu Sukabumi - Bogor by using a differential semantic measurement system. Then the data that has been obtained is carried out several tests such as validity and reality tests, then a classical assumption test is carried out, which is then analyzed with the help of SPPS 23 software to answer the hypothesis in this study. The results of the study show that there is a positive and significant influence between workload and green human resource management on employee performance and by reducing workload and implementing green human resource management can improve the performance of employees of PT. ASTRA INTERNATIONAL Tbk Isuzu Sukabumi - Bogor.